Probing Digital Media Usage at State Islamic Colleges in North Sumatera; from Advantages to Challenges - Sokhira Linda Vinde Rambe; Yusni Sinaga (Universitas Islam Negeri Palopo, 2025)
Utilizing digital media platforms have been obligated for all educators including lecturers to face the educational development. However, there are still many lecturers who are not familiar with their advances and not ready with their usages in teaching. The objectives of this study are to see types of digital media platforms applied by the lecturers and to know advantages derived and challenges faced. The research was done with descriptive qualitative method and 13 English lecturers from the State Islamic Colleges in North Sumatera were chosen purposively as research respondents. To get the data needed, questionnaires were distributed, and interviews were done to respondents. To analyze the questionnaires data, the frequencies as well as percentages were counted, and data reduction, description, display, and conclusion were done to analyze interview data. This study found WA Group is the most preferred platform by the lecturers in blended learning followed by Google Meet, Zoom, Google Classroom, and Quizizz as well as Kahoot. Then, it is revealed that digital media help learners to have lots of interaction with peers and digital media also can motivate lecturers to develop their teaching professionalism. Finally, this research gives some contribution mostly to students and lecturers about types of digital media as well as the advantages of using digital media in teaching and learning process and it informs some challenges faced by students and teachers in making use of the digital media.